An Analysis of Student Participation in Marketing Management Through Project Based Learning Model - Fiardilla, Fauziah; Arisandi, Meri; Yernisa, Yernisa; Sirait, Jeliana Veronika (Journal of Educational Sciences, 2025)
This research was motivated by the low ability of students to think related to problem solving and student activity. Project-based learning will be implemented which is expected to increase student understanding, develop problem-solving skills, increase cooperation abilities and student activity in the learning process. The type of research used is quantitative descriptive. The subjects in this research were 12 students in the 2023/2024 Odd. Data collection techniques used include observation, portfolio, and documentation. The data collection instrument used was a activity observation sheet in Project I and Project II. The data analysis technique uses quantitative data analysis. The criteria for the success of this research can be seen from the increase in the value of student participation in the Marketing Management class. The results of this research indicate an increase in the value of student participation activities by the implementation of Projects I and II. In project I learning activities, the average value of student participation was 77.25. Then there was an increase in the value of participatory activities in project II learning activities to 80.9. Based on these results, it can be concluded that student participation can be increased by implementing the project-based learning model.